Model Pengembangan Ekonomi Pondok Pesantren - Suwito NS (Badan Litbang dan Diklat Kementerian Agama RI, 2008)
The emergence of economic business in pesantrens was driven by their necessity to survive. For that reason, pesantrens needed to run economic activities. The activities were determined by: (a) the ability of kyai to read, define, utilize, and organize their resources, (b) geographical condition, and (c) social and cultural condition, both inside and outside the institutions. Almost all pesantrens in this research ran agribusiness, especially on-farm project. There were only three pesantrens that ran service business. Meanwhile, four pesantrens ran trade business and three pesantrens concerned with industry.